Uma proposta de introdução do aplicativo calculadora gráfica do geogebra para alunos do ensino médio - Nogueira, Gabriel Nunes (Universidade Federal de São Carlos, 2019)
This dissertation presents the idealization, the application and the results of activities using the application "GeoGebra Graphing Calculator" for students of first and third years of high school in two schools in São Paulo State, Brazil, linked to Technical Education, addressing basic content of Analytical Geometry involving Points and Straight Lines. As an additional product of this work, several video lessons were developed to give virtual support to the idealized activities.
A proposal for the introduction of the geogebra graphic calculator application for high school students
Keywords: Calculadora gráfica; GeoGebra; Ensino médio; Geometria analítica; Videoaulas; Calculator; High school; Analytical geometry; Video lessons; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO